Experimental investigation of the effects of supercritical carbon dioxide on fracture toughness of bituminous coals. (July 2018) - Yang, Jianfeng; Lian, Haojie; Liang, Weiguo; Nguyen, Vinh Phu; Chen, Yuedu
Abstract: Effects of supercritical carbon dioxide (scCO2 ) on fracture toughness of bituminous coals are studied. The semi-circular specimens under three-point bending (SCB) were adopted for conducting experiments on the coal samples after being immersed in scCO2 for different soaking periods. To investigate the fracture toughness in different loading conditions, including pure mode I, pure mode II, and mixed mode I/II, the inclination angles of the prefabricated cracks in the coal SCB samples were set as 0°, 5°, 15°, 30°, 45° and 54°, respectively. The experimental results show that after being soaked in scCO2 for 7 days, 14 days and 21 days, the pure mode I fracture toughness of the coals reduced by up to 30.8%, 69.2% and 82.1%, respectively, and the mode II fracture toughness 29.1%, 66.7% and 79.9%, respectively. The fracture toughness in pure mode I loading is more sensitive to the effect of scCO2 than that in pure mode II loading. The values of the effective fracture toughness K eff in mixed mode I/II loading also declined due to the effect of scCO2, and the samples with different crack inclination angles exhibited no obvious differences in the degradation degrees of K eff . With increasing soaking time, the compaction stage extended, and the slope of the load–displacement curve in the elastic stage decreased significantly. The microcracks on the surface of the coal SCB specimens gradually increased with the soaking time increasing. In addition to causing the reduction of surface energy and swelling of coals, scCO2 mobilizes organic molecules from coals, leading to the modification of the physical structure of the coal matrix and the degradation of fracture toughness in various loading modes. Based on the modified maximum tangential stress (MMTS) criterion, which takes into account the effects of T-stress, the theoretical values are in better agreement with experimental results compared with the traditional maximum tangential stress (MTS) criterion. Highlights: The effects of supercritical carbon dioxide on fracture toughness of bituminous coals were investigated. The fracture toughness of coals reduces with soaking time in scCO2 . The theoretical values based on the modified MTS criterion are in good agreement with experimental results.